Sistem Informasi Manajemen Pelanggaran dan Sanksi Otomatis Berbasis Poin Terintegrasi WhatsApp Gateway - Haritsyah, Al Hafiz; Alda, Muhamad (LPPM Universitas Mulia, 2025)
This study aims to design and develop a point-based Automatic Offense and Sanction Management Information System integrated with a WhatsApp Gateway module at SMK Negeri 1 Percut Sei Tuan. The research is motivated by the current use of a manual student offense recording system by counseling teachers, which causes delays in both handling violations and delivering information to parents. The proposed system enables real-time offense recording, automatic sanction determination based on accumulated points, and instant notification delivery to parents via WhatsApp. The system was developed using the Rapid Application Development (RAD) methodology and employed a descriptive quantitative research approach. Data were collected through interviews, observations, and literature reviews. The implementation results indicate that the system improves the efficiency of counseling teachers’ work, reduces the average information delivery time from two working days to less than five minutes, and enhances transparency and accountability in enforcing student discipline. The system features include a dashboard, offense input interface, automatic point calculation, and WhatsApp API-based notification delivery. It is expected that this system will strengthen communication between schools and parents and serve as a model for integrating technology into the education sector.